LOGIKA FUZZY SWARM INTELLIGENCE BEE COLONY UNTUK MEMINIMALISASI KEMACETAN TRANSPORTASI - Andriyani, Widyastuti; Wardoyo, Retantyo (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
This paper uses the concept of fuzzy logics to integrate with bee systems to solve inexact model problems. As an example, in this paper the integration will be used to minimalise the congestion of transportation problems. Bee systems face many problems for decision making when seeking for the best solution, some of them: to determine the next solution components to be added to partial solution, to determine which partial solutions should be left or not, and to determine the same partial solutions without recruiting friends from the same nest. The majority of these selection models is based on the assumption that the decision makers have the ability of processing perfect information, and are always acting rationally and exactly. However, in certain conditions, information is not exact, but is still realistic.